Generation of Flat-Top Q-Switched Envelope Dissipative Soliton Resonance Pulse in Passively Mode-Locked Fiber Laser - Long Han; Tianshu Wang; Runmin Liu; Wanzhuo Ma; Yiwu Zhao; Qiang Fu; Huilin Jiang (IEEE Photonics Journal)
We present demonstration of an erbium-doped fiber laser based on the nonlinear amplifying loop mirror mechanism, with a stable phenomenon of flat-top Q-switched mode-locked (FT-QML) dissipative soliton resonance (DSR) pulse, for the first time. In the experiment, we can observe both the flat-top Q-switched envelope and square-wave pulse by the peak power clamping effect inside the cavity. The characteristics of both continuous DSR pulse and flat-top Q-switched mode-locked square-wave are analyzed comprehensively. With the maximum pump power of 363 mW, single pulse energy in the FT-QML envelope can be up to 14 nJ as three times high as the one of continuous DSR. Essentially, the temporal width of the Q-switched mode-locked envelope can reach 4.6 μs with flat-top duration of 3.5 μs. The amplitude fluctuation of the sub-pulse inside the flat-top is stable at about 0.12% by using the formula of RMSE. Therefore, the laser can provide flat-top burst mode pulse sequence, and the pulse width can be controlled by tuning the pump power.